Epidemiology of Streptococcus pyogenes disease before, during, and after COVID-19 Pandemic, Germany, 2005-2023 - Burckhardt, Irene; Burckhardt, Florian (Emerging infectious diseases, 2024)
We analyzed 3,081 invasive and noninvasive Streptococcus pyogenes cases (January 2005–December 2023) at a tertiary care hospital in southwest Germany. Absolute numbers of case-patients increased each year from 2005 until the COVID-19 pandemic. Odds ratios for invasive streptococcal disease were significantly influenced by year, male sex, and older age.
Gesehen am 02.04.2025